Between a flock and a hard place - Andrews, Donna (Andrews, Donna. Meg Langslow mysteries, 2024)
"Readers will flock to New York Times bestselling author Donna Andrews's next installment in the award-winning Meg Langslow series. Meg's neighbors, the Smetkamps', have won a makeover for their old home from Marvelous Mansions, a flashy, yet dubious company, focused on making historic homes more "modern." The company already several days into its makeover of the Smetkamps' house, and tensions are running high--not only between the officious, demanding Mrs. Smetkamp and her neighbors, but also between her and the renovation crew. Meg, who is trying to keep the peace and prevent the makeover crew from trampling on every clause of the county's building code, arrives at the Smetkamps to find that Caerphilly's resident flock of feral turkeys has moved into their yard--or been relocated there by someone who wanted to cause them trouble. The turkeys are huge, territorial, cranky and aggressive - and impossible to move! Meg does what she can to calm down the irate neighbors and help the makeover crew make progress in spite of the turkeys. She comes up with a plan to gather a group of turkey wranglers to snatch them early in the morning. But when they arrive, they find the body of Mrs. Smetkamp in her backyard. Someone stabbed her, and then tried to make it look as if she was attacked by one of the turkeys, but Meg, the Chief, and the Sheriff are not fooled. Together, they must figure out what really happened to Mrs. Smetkamp...and what to do with all these turkeys!"--